Turbo Codes For Error Control In JPEG Image Transmission - Ramasamy, K. (2005)
The focus of the work is on the performance study, design and weight distribution analysis of convolutional turbo code and turbo product codes. It includes investigation of vital components that influence convolutional turbo code performance, such as constituent encoders and the interleaver. This work begins with the investigation of various iterative decoding techniques, and performance and complexity comparison.